Sports injuries prevention, treatment and rehabilitation - Peterson, Lars; Renstrom, Per A.F.H; Lynch, Scott
As more people realize the cardiovascular, metabolic and muscular benefits that regular physical activity provides, the risk for potential injury also increases. To provide successful treatment, all persons involved in the management of injuries must have a thorough understanding of the healing process of the various tissues and also be familiar with the demands of different types of sports. Written by three world-renowned experts, Sports Injuries, fifth edition, comprehensively covers the prevention, treatment and rehabilitation of sports injuries. Essential reading for all athletes, coaches/trainers, physiotherapists and doctors, the updated edition of this highly popular and well-established textbook skillfully integrates scientific background and evidence with practical application. Updated topics covered include: Individual risk factors for sports injuries; Effects of physical inactivity on the tissues; Head and face injuries in sport; Cervical, thoracic and abdominal injuries in sport; Back and spine injuries in sport; Leg knee and thigh injuries; Outdoor activities during extreme conditions; Ethical considerations in sports and exercise medicine; Injuries in sport for the disabled, growing and aging athletes. Richly illustrated with more than 600 color drawings and photographs, this covers injuries resulting form the full range of international sports. For each type of injury examined, it details the symptoms, mechanism of injury, diagnosis, treatment, rehabilitation protocols and key points - clearly stating what both non-medical and medical professionals should do in each case of injury. This easy-to-follow textbook features a glossary of key terms and protocols with rehabilitation exercises to provide readers with a solid understanding about how to effectively treat, rehabilitate and prevent sports injuries. This book will be of key reading to academics and students of key reading to academics and students of sport medicine, sport injury, physiotherapy and sports rehabilitation as well as related disciplines